1980
DOI: 10.1159/000198460
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Response to Ursodeoxycholic Acid for Gallstone Dissolution

Abstract: 20 patients with radiolucent gallbladder stones were reviewed after 6 months’ treatment with ursodeoxycholic acid (UDCA) at a dose of either 500 or 1,000 mg daily. Successful treatment could not be predicted from the patients’ characteristics, nor from stone size or pre-treatment biliary lipid analysis. During treatment the bile in patients who responded to UDCA differed from bile in those who did not: mean cholesterol content was lower in responders (4.1 ± 0.6 vs. 5.7 ± 0.5 mol%, p < 0.025) as was the lithoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Biliary lithocholic acid was partly present as sulfate ester. In the control period, 27 (1)(2)(3)(4)(5)(6)(7)(8)(9). In one study, the high dose resulted in more rapid gallstone dissolution (8).…”
Section: Biliary Cholesterol (mentioning
confidence: 99%
See 2 more Smart Citations
“…Biliary lithocholic acid was partly present as sulfate ester. In the control period, 27 (1)(2)(3)(4)(5)(6)(7)(8)(9). In one study, the high dose resulted in more rapid gallstone dissolution (8).…”
Section: Biliary Cholesterol (mentioning
confidence: 99%
“…Urso treatment leads to dissolution of cholesterol gallstones in man (1)(2)(3)(4)(5)(6)(7)(8)(9). Oral administration of Urso increases Urso in bile and decreases the biliary cholesterol (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop a better understanding of the interaction between bile acids and gallstone formation, individual bile acids from animals within each dietary group were analyzed. This was particularly important, because bile acids such as ursodeoxycholic, chenodeoxycholic and hyodeoxycholic acid have been shown to have the ability to dissolve gallstones when administered in the diet of humans (10)(11)(12)(13)(14)(15)(16)(17)(18). The present study seems to indicate that dietary proteins may have an effect on gallstone formation by altering concentrations of specific bile acids in hamsters.…”
Section: Effect Of Dietary Proteins On Biliary Lipids Studies In-mentioning
confidence: 66%
“…It is generally accepted that the abnormality which leads to formation of lithogenic bile involves an insufficient concentration of bile acid and/or phospholipid to prevent biliary cholesterol from precipitating out of solution. Several studies using human subjects (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) have shown that the bile acid/phospholipid/cholesterol ratio can be altered by feeding chenodeoxycholic acid and thereby dissolving cholesterol gallstones. Ursodeoxycholic acid consumption has also been shown to be effective in dissolving cholesterol gallstones in humans (18) and hamsters (19).…”
mentioning
confidence: 99%